OPTIMASI WAKTU QUERY DAN FILTERING NAMA DOMAIN PADA DNS SERVER LOKAL MENGGUNAKAN BIND 9 - Dian Novianto (UNIVERSITAS INDO GLOBAL MANDIRI)
DNS is made to facilitate users in accessing a website with a domain without having to continually update the files host.txt.DNS was developed in 1983, every user accessing a website using a domain name through a browser, will be routed by the router to a public DNS serverto get a web address in the form of ip address.It takes time for DNS servers to reverse and lookup for translate domain names into ip addresses and vice versa.By creating a local DNS server as a cache,then it can be applied forwarding technique on DNS Server,so the time required to find the web server address of a destination website becomes faster. In addition to minimizing query time by implementing a local DNS server, can also be filtered against a particular domain name even though using a secure protocol like httpsby creating a zone for the web address you want to filter. So the use of the Internet becomes more useful. In this study the software used linux debian 8 as the operating system, and BIND9 as the software that runs the function of DNS Server.Keywords:Forwarding DNS,BIND 9, Debian 8